Examining the role of entrepreneurial universities in regional development - Daniel, Ana Dias (IGI Global, 2019)
Universities are becoming more entrepreneurial, and for local communities and companies, this has increased their economic standings tenfold. However, the competitiveness of developing economies thanks to these financially focused institutions has likewise increased. Examining the Role of Entrepreneurial Universities in Regional Development provides emerging research exploring how universities foster and support entrepreneurship and the development of a more entrepreneurial organization and highlights the importance of this process for local communities and companies. Featuring coverage on a b.